2012
DOI: 10.1155/2012/839724
|View full text |Cite
|
Sign up to set email alerts
|

Anterior and Posterior Meniscofemoral Ligaments: MRI Evaluation

Abstract: Although meniscofemoral ligaments are distinct anatomic units, their anatomy and function are controversial from an anatomic and radiologic point of view. Five hundred knee MR examinations were retrospectively studied in an effort to demonstrate the incidence and variations regarding sex and age distribution, as well as the anatomy of the meniscofemoral ligament at magnetic resonance imaging. Patients were mostly men, three hundred and twelve, in contrast with women who were fewer, one hundred eighty-eight pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 17 publications
1
21
2
Order By: Relevance
“…There is no literature about the age correlation with MFL CSA, but several authors have noted a possible degeneration of the MFLs with age [ 7 , 8 ] or have reported diminishing tensile strength in elderly populations [ 6 ], which may be explained by a thinning of the ligaments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no literature about the age correlation with MFL CSA, but several authors have noted a possible degeneration of the MFLs with age [ 7 , 8 ] or have reported diminishing tensile strength in elderly populations [ 6 ], which may be explained by a thinning of the ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this documented variability may be found in the work of Woo et al [ 6 ], who showed that the ligaments in the knee joint were significantly stronger in young adults than in the elderly. Age-related degeneration of the MFLs would involve not only a weakening of the MFL structure, but also the possible eventual disappearance of the MFLs, as studies have also suggested [ 7 , 8 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…According to Watanabe et al 2) , 32.5% of the meniscofemoral ligaments were present with Wrisberg ligament and 33% were present with Humphrey ligament and seen either as a discrete low signal-intensity bulge or a lump along the concave surface of the PCL or as a small, ovoid, low signal intensity focus just anterior to the PCL. In a study performed by Bintoudi et al 3) , only 81 among 500 patients (37%) presented both meniscofemoral ligaments and in other studies of Moran et al 4) and Lee et al 5) , the percentage was 28% and 1%, respectively. Erbagci et al 6) did not reveal the incidence.…”
Section: Discussionmentioning
confidence: 85%
“…The high-risk sources of bias primarily pertained to 1 domain (methodology characterization), which has previously been identified as a source of variability. 11 , 32 …”
Section: Resultsmentioning
confidence: 99%